Feminism - Saul, Jennifer Mather (Oxford University Press, 2003)
Filling a gap in the textbook market, Feminism: Issues & Arguments provides an accessible and stimulating introduction to feminist philosophy that assumes no background in the subject. Drawing on both philosophical thought and up-to-date empirical research, Jennifer Mather Saul provides lucid arguments for a variety of feminist positions but avoids advocating any particular position so that students will be motivated to think critically. The chapters are organized around key topics including pornography, abortion, sexual harassment, and the politics of work and family. By focusing on real-world applications of feminist philosophy, this text brings the subject to life for students because it deals with issues that they care about. Feminism: Issues & Arguments is ideal for courses in feminism, feminist philosophy/philosophy of women, and sociology of women